"The future of an illusion": a paradoxes of CSR. Issue 1 (11th February 2019) - González-González, José María; Bretones, Francisco D.; González-Martínez, Rocío; Francés-Gómez, Pedro
Abstract : Purpose: The purpose of this paper is to explore the psychological strategies as well as the rhetorical and discursive arguments developed in organizations and by individuals when they have to cope with the paradoxes and changes related to CSR. Design/methodology/approach: This study uses the perspective of the paradox as an analytical framework to parse strategies developed in organizations as they cope with tensions and changes related to CSR. The authors conducted 50 semi-structured interviews with stakeholders and the authors performed a qualitative analysis with the information compiled. Findings: The main strategies for dealing with CSR paradoxes and changes consist of developing perceptual and motivational biases as well as explicative heuristic ones through which, from a discursive perspective, a coherent and conciliatory framework is presented with rhetoric that play a fundamental role in justifying CSR as a present hope over a future illusion regardless of the past reality. Originality/value: The lesson to be drawn from the exploration is the following: managers and CSR officers need to leave behind fear, anxiety and defensive attitudes and accept the paradox by re-contextualizing the tension as a stimulus for conscious and reflexive confrontation with emotional equilibrium, this being defiantly motivating as a sensemaker. In this way, the approach to the present inconsistencies in CSR should not involve a dismissal of conflictive situations but rather the development of the capacity to transcend the tension emanating from them and to learn to manage organizations from this paradoxical reality.